The Impact of Waste Bank on Waste Processing Behavior and Income - Choirrunnisa, Diana; Ngatindriatun, Ngatindriatun (Universitas Negeri Semarang, 2021)
Waste bank is a solution to reduce waste problems because the only environmentally based waste management is done by sorting waste into something that has economic value. The purpose of this study was to determine and analyze the impact of waste bank activities and waste bank leadership on household waste processing behavior. This study used a quantitative approach. The type of data was primary data. This research was conducted with 99 waste bank customers with the respondent determination technique using Proportional Stratifed Random Sampling from the presence of customers in one month to 2 to 4 times saving waste. Regression analysis and T-test difference test using SPSS 21 were employed to analyze the data. Based on the findings, main waste bank in East Jakarta had an impact on breaking the chain of waste prices. The existence of a waste bank which is measured based on cognitive, affective, and psychomotor aspects has a positive effect on people's behavior in managing waste in their environment. This study also showed that there was a difference in the average income of the community after becoming a customer of a waste bank. Bank sampah merupakan solusi untuk mengurangi permasalahan sampah karena satu-satunya pengelolaan sampah berbasis lingkungan yang dilakukan dengan memilah sampah menjadi sesuatu yang mempunyai nilai ekonomis. Tujuan penelitian ini adalah untuk mengetahui dan menganalisis dampak kegiatan bank sampah dan kepemimpinan bank sampah terhadap perilaku pengolahan sampah rumah tangga. Penelitian ini menggunakan pendekatan kuantitatif. Jenis data adalah data primer. Penelitian ini dilakukan dengan 99 onasabah bank sampah dengan teknik penentuan responden menggunakan Proportio Stratifed Random Sampling dari kehadiran nasabah dalam satu bulan mencapai 2 sampai 4 kali menabung sampah. Metode penelitian ini analisis regresi dan uji beda T-test menggunakan SPSS 21. Bank sampah Induk di Jakarta Timur juga memberikan dampak memutus mata rantai harga sampah. Keberadaan bank sampah yang diukur berdasarkan aspek kognitif, afektif, dan psikomotorik berpengaruh positif terhadapperilaku masyarakat dalam mengelola sampah di lingkungannya. Penelitian ini juga menunjukan bahwa terdapat perbedaan rata-rata pendapatan masyarakat sesudah menjadi nasabah bank sampah.